How can we value what is not measured: the need for better data on women’s health and primary care - Fiona Imlach; Natalia Boven; Vanessa Selak (New Zealand Medical Journal, 2026)
Decisions about healthcare funding and delivery in Aotearoa New Zealand, as well as the monitoring of health service performance and outcomes, are driven by readily available data, in particular from administrative health datasets. Most of these national health data collections are generated through the delivery of secondary health services. Further, apart from hospitalisation and mortality collections, these lack diagnostic coding, rendering the burden and cost of chronic health conditions predominantly managed in primary care largely invisible. Many of these types of health conditions disproportionately affect women, who, despite their longer life expectancy, spend 25% more time in poor health than men, according to international research on the women’s health gap. This gap is driven by conditions occurring only in women (e.g., premenstrual syndrome, endometriosis, polyendocrine metabolic ovarian syndrome) or with higher burden in women (e.g., anxiety, depression, migraine). Addressing this gap could add US$1 trillion to the global economy. In Aotearoa New Zealand, major improvements in national health data collections are urgently needed to assess the cost of the women’s health gap and the burden of chronic diseases that have high social and economic impact but are undetectable or difficult to survey in our existing administrative datasets. We illustrate these issues using the example of migraine disease, the most disabling neurological condition in Australasia that also affects at least twice as many women as men.